1996
DOI: 10.1002/etc.5620150509
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of polycyclic aromatic compounds of different molecular size and water solubility in surficial sediment of an intertidal sandflat

Abstract: Abstract-The persistence of 13 polycyclic aromatic hydrocarbons (PAHs), ranging from two-to six-ring compounds, in an intertidal sandflat was studied by applying uniform amounts (0.10 g) of each to the surface of the sandflat and then monitoring concentrations over time. The mass of total PAH, after initial losses, declined slowly, so that after 256 d 12% of the applied material remained. Vertical concentration profiles indicated that little downward movement occurred and that most of the mass was concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Perkin Elmer Elite-5HT capillary column (5% diphenyl, 95% dimethyl polysiloxane) was used (Aderemi, 2003;Wilcock et al, 1996). Data acquisition and analysis were performed using Perkin-Elmer Turbochrom data acquisition and analysis software.…”
Section: Analysis Of Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…Perkin Elmer Elite-5HT capillary column (5% diphenyl, 95% dimethyl polysiloxane) was used (Aderemi, 2003;Wilcock et al, 1996). Data acquisition and analysis were performed using Perkin-Elmer Turbochrom data acquisition and analysis software.…”
Section: Analysis Of Polycyclic Aromatic Hydrocarbonsmentioning
confidence: 99%
“…In our study we mostly found tetra and pentacyclic congeners. Generally, an increase in the size of a PAH molecule results in an increase in electrochemical stability [39] which in turn contribute to the persistence of PAHs in the environment [40]. As BDE 47 and BDE 99, the PAHs we found in the Italian site as fluoranthene have a high potential for biomagnification and are known to exert toxic effects and possess mutagenic or carcinogenic properties [41].…”
Section: Hexachlorobenzene (Hcb) and Isomers And Metabolites Of Dichlmentioning
confidence: 99%
“…Biodegradation of benzo[a]pyrene in long-term contaminated soil by indigenous microorganisms has usually been considered to be a very long-term process (Bossert et al 1984 , 1986 ; Coover et al 1987 ; Keck et al 1989). The half-life of benzo[a]pyrene in soil ranges from 100 days to 14.6 years (Wild et al 1991 ; Wilcock et al 1996 ). It was therefore surprising that about 78% of soil benzo[a]pyrene was dissipated during the 60 days of cultivation in the present study, and the organisms degrading benzo[a]pyrene in this soil deserve further study.…”
Section: Discussionmentioning
confidence: 99%